Regulation of cardiac fibroblast cell death by unfolded protein response signaling - Rowland, Mary B.; Moore, Patrick E.; Correll, Robert N. (Frontiers in Physiology, 2024)
The endoplasmic reticulum (ER) is a tightly regulated organelle that requires specific environmental properties to efficiently carry out its function as a major site of protein synthesis and folding. Embedded in the ER membrane, ER stress sensors inositol-requiring enzyme 1 (IRE1), protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK), and activating transcription factor 6 (ATF6) serve as a sensitive quality control system collectively known as the unfolded protein response (UPR). In response to an accumulation of misfolded proteins, the UPR signals for protective mechanisms to cope with the cellular stress. Under prolonged unstable conditions and an inability to regain homeostasis, the UPR can shift from its original adaptive response to mechanisms leading to UPR-induced apoptosis. These UPR signaling pathways have been implicated as an important feature in the development of cardiac fibrosis, but identifying effective treatments has been difficult. Therefore, the apoptotic mechanisms of UPR signaling in cardiac fibroblasts (CFs) are important to our understanding of chronic fibrosis in the heart. Here, we summarize the maladaptive side of the UPR, activated downstream pathways associated with cell death, and agents that have been used to modify UPR-induced apoptosis in CFs.